Prevalence and prognostic implication of iron deficiency and anaemia in patients with severe aortic stenosis - Kvaslerud, Anette Borger (Open Heart, 2018)
OBJECTIVE: The aim of this study was to evaluate the prevalence and prognostic implication of iron deficiency (ID) and anaemia in patients with severe aortic stenosis (AS). METHODS: In an observational study of consecutive patients referred for aortic valve replacement (AVR), we assessed a wide range of biomarkers of iron status, including the definition of ID commonly applied in patients with chronic heart failure (ferritin <100 µg/L or ferritin 100–299 µg/L with a transferrin saturation <20%). The endpoints were short-term (one-year) and long-term (median 4.7 years, IQR: 3.8–5.5) mortality and major adverse cardiovascular events (MACE) within the first year after inclusion. RESULTS: 464 patients were included in this substudy. 91 patients (20%) received conservative treatment and 373 patients (80%) received AVR. ID was detected in 246 patients (53%). 94 patients (20%) had anaemia. Patients with ID had an overall worse clinical profile than patients without ID. During follow-up, 129 patients (28%) died. Neither ID as defined above, soluble transferrin receptor nor hepcidin were associated with short-term or long-term mortality or MACE independent on treatment allocation. Anaemia was associated with one-year mortality in conservatively treated patients. CONCLUSIONS: ID and anaemia are prevalent in patients with severe AS. In our cohort, ID did not provide independent prognostic information on top of conventional risk factors. More studies are required to determine how to correctly diagnose ID in patients with AS. TRIAL REGISTRATION NUMBER: NCT01794832.